The CARMENES search for exoplanets around M dwarfs: convective shift and starspot constraints from chromatic radial velocities - Baroch, David; Quirrenbach, Andreas; Henning, Thomas (Astronomy and astrophysics, 2020)
Context. Variability caused by stellar activity represents a challenge to the discovery and characterization of terrestrial exoplanets and complicates the interpretation of atmospheric planetary signals.Aims. We aim to use a detailed modeling tool to reproduce the effect of active regions on radial velocity measurements, which aids the identification of the key parameters that have an impact on the induced variability.Methods. We analyzed the effect of stellar activity on radial velocities as a function of wavelength by simulating the impact of the properties of spots, shifts induced by convective motions, and rotation. We focused our modeling effort on the active star YZ CMi (GJ 285), which was photometrically and spectroscopically monitored with CARMENES and the Telescopi Joan Oró.Results. We demonstrate that radial velocity curves at different wavelengths yield determinations of key properties of active regions, including spot-filling factor, temperature contrast, and location, thus solving the degeneracy between them. Most notably, our model is also sensitive to convective motions. Results indicate a reduced convective shift for M dwarfs when compared to solar-type stars (in agreement with theoretical extrapolations) and points to a small global convective redshift instead of blueshift.Conclusions. Using a novel approach based on simultaneous chromatic radial velocities and light curves, we can set strong constraints on stellar activity, including an elusive parameter such as the net convective motion effect.